Physalis pubescens L. branch and leaf extracts inhibit lymphoma proliferation by inducing apoptosis and cell cycle arrest - Yuan-Ce, Li; Yu-Yan, Pang; Qi, Zhang; Hong-Yang, Zhang; Yan-Wen, Wang; Yu-Mei, Sun; Guang-Zhi, Zeng; Jun-Lin, Yin (Frontiers in Pharmacology, 2023)
Physalis pubescens L. is an annual or perennial plant in the family Solanaceae. It is used in traditional medicine for treating sore throats, coughs, urinary discomfort, and astringent pain, and externally for pemphigus and eczema in northern China. The proliferation inhibitory activity and mechanisms of the ethyl acetate extract (PHY-EA) from the leaves of P. pubescens were investigated. High performance liquid chromatography was used to identify the chemical composition of PHY-EA; sulforhodamine B was used to detect the proliferation inhibitory effect of PHY-EA on MCF-7, CA-46, Hela, HepG2, B16, and other tumor cells; flow cytometry was used to detect the effect of PHY-EA on the lymphoma cell cycle and apoptosis; Western blot was used to detect the expression of the cycle-and apoptosis-related proteins. The expression of Ki-67 and cleaved caspase 3 was detected by immunohistochemistry. The results showed that PHY-EA contained physalin B, physalin O, and physalin L. PHY-EA blocked the cell cycle of G2/M→G0/G1 in lymphoma cells and induced apoptosis in tumor cells. Mouse transplantation tumor experiments showed that PHY-EA had a significant inhibitory effect on mouse transplantation tumors, and the tumor volume and weight were significantly reduced. In conclusion, PHY-EA has a good antiproliferative effect on Burkkit lymphoma, indicating its potential medicinal value.